HUBUNGAN POWE OTOT LENGAN DENGAN KEMAMPUAN PUKULAN LURUS PADA CABANG OLAHRAGA BELA DIRI PENCAK SILAT DESA LOMBU JAYA, KECAMATAN SAWERIGADI, KABUPATEN MUNA BARAT - Halfin Halfin; Wolter Mongsidi; Muh. Rusli (JOKER (Jurnal Ilmu Keolahragaan), 2020)
The formulation of the problem is "Is there any correlation between Arm Muscle Power to the Ability of Straight Punch on Pencak Silat Martial Arts Organization in Lombujaya Village, West Muna Regency?. The purpose of this study was to determine the correlation of arm muscle power to the punch ability straight on Pencak Silat Organization (PO) martial arts in Lombujaya Village, West Muna Regency. The populations of this study are all athletes who trained, the total is 40 people. Then the samples are 30 athletes who actively practiced it.The instrument that used to measure the arm muscle power was using a medicine ball-put test with a weight of 3 kg while to measure the ability of straight punch of pencak silat was using 30 seconds punch frequency test, and the techniques of data analysis was using product moment analysis.Based on the significant value 0.00 < 0.05, so it can be concluded that there is a correlation between the independent variable to dependent variable. The correlation value between arm muscle power with the ability of punch straight in pencak silat can be seen that rxy = 0.74> r (0.05) (30), it means that there is a significant correlation between the two variables or can be said that it has a very strong correlation and have a positive correlation, if we convert it into correlation map so it is include in high correlation. The coefficient of determination, r 2 = 0, 54 in other words 54% of the ability of punch straight in pencak silat is determined by the muscle power of arm while the other, 46% is determined by other physical conditions.